INNOVATIVE APPROACHES TO MANAGEMENT OF THE INSURANCE COMPANY SOLVENCY IN UKRAINE - Dranus В.; Dranus Л.; Trushkina Н. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2023)
Insurance aims to attract and accumulate funds by insurers to fulfill their obligations to their customers, as well as to further invest in the expansion of insurance activities and development of the country’s economy. The successful operation of insurance companies largely depends on the level of their financial conditions, i.e. financial stability and solvency. The financial conditions of an insurance company are characterized by indicators that describe its ability to develop and operate successfully in the competitive market environment. The stable financial conditions of an insurer are the key to development in the market economy and ensure sustainability of the country’s insurance market. The principal differences between the categories of “financial stability” and “solvency” of an insurer are characterized in the work. It is noted that there is no consensus in scientific publications on the definition of “solvency”, and theoretical approaches to the definition of this concept are analyzed. In addition, in their proposals not all researchers consider presence of the insurance component. The authors argue for the need to introduce innovative approaches to the indicators of assessing the financial stability and solvency of insurance organizations. The insurance market in Ukraine is in the process of improvement and development. Integration into the European Union and implementation of directives contribute to improvement of insurance. The article analyzes the need to introduce new EU directives regulating the insurance market and methods for assessing an insurer's solvency. It is determined that one of the features of the new regulations of the EU Directives is a risk-oriented approach to assessing solvency of an insurer. The authors compare the principles of insurer solvency assessment under the two approaches, namely Solvency I and Solvency II, identify their requirements, mechanisms for their implementation, and also outline prospects and possible difficulties in implementing this methodology for assessing solvency in the practical activities of insurance companies.